Preparation and metatranscriptomic analyses of host-microbe systems - Hampton-Marcell, Jarrad T; Moormann, Stephanie M; Owens, Sarah M; Gilbert, Jack A (Methods in enzymology, 2013)
Metatranscriptomics has increased our working knowledge of the functional significance and genetic variability of microbial communities, yet there is still limited information concerning how gene expression and regulation in a microbiome influences interactions with a host organism. During a pathogenic infection, eukaryotic organisms are subject to invasion by bacteria and other agents, or these "pathogens" can switch from a commensal to pathogenic trophic relationship with the host. Understanding how these trophic relationships initiate and persist in the host requires deciphering the functional response of the host and the microbiome, so-called Dual RNA-Seq. This technique is both fast and relatively cheap compared to proteomics and metabolomics and provides information on the potential functional interactions that occur between microbes, and with the host. These metatranscriptomic analyses can also be coupled with metagenomic analyses and statistical models to provide an in-depth approach to systems biology. In this chapter, we detail a standardized method to process and analyze host-associated microbial metatranscriptomes independent of the associated host.